Development of response surface methodology for optimization of congo red adsorption utilizing exfoliated graphite as an efficient adsorbent - Pham, Thinh Van; Tran, Thuan Van; Nguyen, Trinh Duy; Tham, Nguyen Thi Hong; Quang, Phan Thanh Tri; Uyen, Dao Thi To U; Le, Nhan Thi Hong; Vo, Dai-Viet N.; Thanh, Nguyen Trung; Bach, Long Giang (Elsevier Ltd, 2019)
In the present study, we developed an optimization model of CR adsorption onto EG using response surface methodology (RSM) as a statistical tool. The EG was structurally characterized using several techniques such as scanning electron microscope (SEM), estimation of N2 adsorption/desorption isotherm and plotting of pore size. The EG was used as adsorbent to remove the CR from water. Three variables involving concentration (20-50 mg/L), pH (4-10), adsorption time (0-210 min) were investigated. To find out the optimal condition, we adopted Design Expert software-based RSM for the experimental design, 3D surface plotting, and optimization. The optimal results were found at concentration of 48.3 mg/L, and contact time of 188 min for the highest CR adsorption capacity at 53.423 mg/g. With high compatibility via confirmation test, it is suggested that the RSM can be the suitable method to optimize the adsorption of CR onto EG.